Adenosine A2A Receptor Stimulation Inhibits TCR-Induced Notch1 Activation in CD8+T-Cells - Sorrentino, Claudia; Hossain, Fokhrul; Rodriguez, Paulo C.; Sierra, Rosa A.; Pannuti, Antonio; Hatfield, Stephen; Osborne, Barbara A.; Minter, Lisa M.; Miele, Lucio; Morello, Silvana (Frontiers in Immunology, 2019)
Notch receptors signaling is required for optimal T-cell activation and function. T-cell receptor (TCR) engagement can activate Notch receptors in T-cells in a ligand-independent fashion. In this study, we examined the role of adenosine A2A receptor (A2AR) signaling pathway in regulating the activity of Notch1 induced by TCR stimulation in CD8+T-cells. A selective A2AR agonist decreased Notch1 protein expression and Notch1 cleavage, and reduced transcripts of Notch1-target genes HES1 and Myc in activated CD8+T-cells. Inhibition of TCR-induced Notch1 expression by an A2AR agonist was accompanied by increased cAMP concentration and mimicked by forskolin. This effect was associated with reduced IFN- and granzyme B production. The effect of an A2AR agonist was abrogated by a selective A2AR antagonist and absent in CD8+T-cells harvested from A2AR-/- mice. Stimulation of A2AR reduced Notch1 receptor levels by inhibiting upstream TCR signals, including ZAP70 phosphorylation, in turn impairing the generation of the active Notch1 intracellular domain (N1ICD). Direct activation of PKC with PMA and ionomycin bypassed A2AR-induced Notch1 inhibition. Overexpression of N1ICD in CD8+T-cells prevented the suppressive effects of an A2AR agonist on proliferation and cytokine release during activation. Our results identify the A2AR signaling pathway as an important regulator of TCR-induced Notch1 receptor activation in CD8+T-cells, and Notch as an important target of the immune suppressive effects of A2AR. We propose a mechanism whereby A2AR impairs CD8 T-cells function through inhibition of Notch1 receptor activation.